Developing a Campus Slang Dictionary for the University of Botswana - Otlogetswe, Thapelo J.; Ramaeba, Goabilwe (Lexikos, 2014)
This paper focuses on the study of slang on a university campus for a lexicographic project. The research was conducted at the University of Botswana, a campus comprising circa 16,000 students, most of whom are bilingual in Setswana and English, and a small population of foreign students. Very few studies and documentations of slang have been attempted in an African context (cf. Alimi and Arua 2008; Arua and Alimi 2009), in particular for lexicographic purposes. It is therefore hoped that this study will contribute to filling this paucity of literature. In general, university campuses are rich in slang since they consist of a closed group of persons. Slang is the use of informal words and expressions that are not considered standard in the speaker's language or dialect. It is not just informal but it is also considered a lower register of the standard language, therefore disapproved of by users of standard language. In addition to being common within a specific group, in this case a student group, slang is also general within an ingroup such as a gang or a clique. Because of it being proscribed, slang is usually absent from many African language dictionaries which are largely prescriptive in their documentation of the language (Otlogetswe 2006). In this paper, the design of a dictionary of campus slang is proposed that would capture the wealth of the slang of a linguistic community. The data used for the proposed dictionary was collected on the University of Botswana campus.